Trend 2000 - 2003. Statistics Canada. CANSIM: Information and Communications Technology - Television and Radio Industries | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-129. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Information and Communications Technology - Television and Radio Industries | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-129. Dataset: Presents statistics on the revenues, expenses, employment, and audiences of radio and television stations and networks in Canada, as well as the revenues, expenses, and employment of and subscriptions to the video and audio services of cable and satellite television operators in the nation. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Telecommunications Services, Broadcasting, Television, Information and Communications Technology, Radio, Telecommunications Industry